Advanced Imaging Colorimetry. Issue 5 (1st September 2015) - Konjhodžić, Đenan; Khrustalev, Peter; Young, Richard
Abstract : Implementing advanced methods of display metrology enables highly accurate luminance and color‐imaging measurements to be performed. The next generation of high‐accuracy imaging colorimeters benefits from a combined approach of recording additional data and utilizing a matrix‐based optimization algorithm.